Dampak Pola Asuh Orang Tua Terhadap Kemandirian Anak (Studi Kasus Di RA Muslimat NU 076 Jalen Ngrukem Mlarak Ponorogo) - syahrudin (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2022)
Early childhood education (PAUD) is a level of education before basic education, which is a coaching effort aimed at children from birth to six years of age. One of the preschool institutions is Raudlatul Athfal who foster children aged 4-6 years. After the child enters that period, the child will begin to learn independently and stand alone apart from the supervision of parents or caregivers. learn to be sociable, adjust to groups and develop openness. Parents play an important role in educating children to have an independent character. In the field, the researchers found that there were students who were in charge of completing children's school assignments who were less independent, less painstaking, impatient, influenced by friends, and careless, and less able to control pocket money. For this reason, it is necessary to increase the child's independence through the implementation of parenting styles. The parenting style applied to children in RA Muslimat NU 076 is democratic parenting. The care includes not imposing the will on the child, not giving full freedom to the child, and considering every child's decision, providing solutions and input to the child, the condition of independence at RA Muslimat NU 076 Jalen Ngrukem Mlarak Ponorogo has been scheduled every day, parents have also striving for children's independence while at home, therefore most children have good independence. The impact of parenting on children's independence, that most parents have implemented democratic parenting for children so that children's independence in RA Muslimat NU 076 Jalen Ngrukem Mlarak Ponorogo is good.